Measurement of Ultraviolet-B (UVB) Minimum Erythema Dosage (MED) Based on Sun Exposure as the Basis of Sunlight Phototherapy: Study of Skin Type III or IV at Various Altitudes in Indonesia - Meidiyanti, Prima; Radiono, Sunardi; Stella, Maureen Miracle; Febiyanto, Novian; Arief Budiyanto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Phototherapy facilities for skin diseases are not widely available in Indonesia. No studies have yet measured the duration of sunbathing to achieve a minimal erythema dose (MED) in healthy volunteers at various altitudes. Purpose: This study calculates the duration of sunbathing to achieve the MED at various altitudes. Methods: This study was conducted in various regions of Yogyakarta, Indonesia, with latitude 7◦15’-8◦15’ S and 110◦5’-110◦4’ E, within the Yogyakarta equinox period by including three places with different altitude groups at 10:00 WIB (UTC+7). Forty-eight healthy individuals of skin type III or IV were exposed to sunlight using a photo-opaque template with 8 squares, each with 1 x 1 cm2 holes. The squares will receive an increase in exposure duration of as many as 250 seconds. Result: There was a significant difference in the mean UVB intensity between all heights (p <0.05). The average duration of sunbathing to reach MED at an altitude of 0-300 masl, > 300-600 masl, and > 600-950 masl are 22 minutes 40 seconds, 20 minutes 34 seconds, and 18 minutes 14 seconds, respectively. There is no significant difference in the duration of sunbathing between altitudes of 0-300 masl and 300-600 masl and between 300-600 masl and 600-950 masl (p> 0.05). However, there was a significant difference in the duration of sunbathing between the altitudes of 0-300 masl and 600-950 masl (p <0.05). Conclusion: A difference exists in the duration of sunbathing required to achieve MED at altitudes greater than 600 masl